Implementasi Moderasi Beragama di Desa Dalan Lidang, Kecamatan Panyabungan, Kabupaten Mandailing Natal - Mardian Idris Harahap; Windi Jihan Nabila; Rizka Nasution; Aida Ulvani Nasution (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This article aims to discuss religious harmony in Dalan Lindang village, Mandailing Natal Regency. Data was collected by means of participatory observation, and secondary data. The results of this study indicate that multicultural life requires understanding and awareness of multiculturalism, religion and others that respects differences, pluralism and willingness to interact with anyone fairly. It requires an attitude of religious moderation in the form of acknowledging the existence of other parties, having a tolerant attitude, respect for differences of opinion and not forcing one's will by means of violence. The role of the government, community leaders, and religious instructors is needed to socialize, develop religious moderation to the community for the realization of harmony and peace.